Characterization of 83-kilodalton nonmuscle caldesmon from cultured rat cells: stimulation of actin binding of nonmuscle tropomyosin and periodic localization along microfilaments like tropomyosin (The Rockefeller University Press, 1988)
Nonmuscle caldesmon purified from cultured rat cells shows a molecular weight of 83,000 on SDS gels, Stokes radius of 60.5 A, and sedimentation coefficient (S20,w) of 3.5 in the presence of reducing agents. These values give a native molecular weight of 87,000 and a frictional ratio of 2.04, suggesting that the molecule is a monomeric, asymmetric protein. In the absence of reducing agents, the protein is self-associated, through disulfide bonds, into oligomers with a molecular weight of 230,000 on SDS gels. These S-S oligomers appear to be responsible for the actin-bundling activity of nonmuscle caldesmon in the absence of reducing agents. Actin binding is saturated at a molar ratio of one 83-kD protein to six actins with an apparent binding constant of 5 X 10(6) M-1. Because of 83-kD nonmuscle caldesmon and tropomyosin are colocalized in stress fibers of cultured cells, we have examined effects of 83-kD protein on the actin binding of cultured cell tropomyosin. Of five isoforms of cultured rat cell tropomyosin, tropomyosin isoforms with high molecular weight values (40,000 and 36,500) show higher affinity to actin than do tropomyosin isoforms with low molecular weight values (32,400 and 32,000) (Matsumura, F., and S. Yamashiro-Matsumura. 1986. J. Biol. Chem. 260:13851-13859). At physiological concentration of KCl (100 mM), 83-kD nonmuscle caldesmon stimulates binding of low molecular weight tropomyosins to actin and increases the apparent binding constant (Ka from 4.4 X 10(5) to 1.5 X 10(6) M-1. In contrast, 83-kD protein has slight stimulation of actin binding of high molecular weight tropomyosins because high molecular weight tropomyosins bind to actin strongly in this condition. As the binding of 83-kD protein to actin is regulated by calcium/calmodulin, 83-kD protein regulates the binding of low molecular weight tropomyosins to actin in a calcium/calmodulin-dependent way. Using monoclonal antibodies to visualize nonmuscle caldesmon along microfilaments or actin filaments reconstituted with purified 83-kD protein, we demonstrate that 83-kD nonmuscle caldesmon is localized periodically along microfilaments or actin filaments with similar periodicity (36 +/- 4 nm) as tropomyosin. These results suggest that 83- kD protein plays an important role in the organization of microfilaments, as well as the control of the motility, through the regulation of the binding of tropomyosin to actin.